Analisis Kebutuhan Instruksional di SDN Kebon Besar 1 - Nur Herni Hernawati Dewi; Nur Suci Ramadhanty; Nur Wilda Akmalia (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
This research intends to understand some of the needs that exist in SDN Kebon Besar 1. And to know some of the weaknesses and advantages of learning needs at the SDN. This observation uses a qualitative descriptive method. The results of the analysis of this study note that the most important learning needs are books, teacher handbooks and student books. If one is inadequate, then the learning process will not run, because the book is a reference in the implementation of the learning process. Next, the most important requirement is the media in learning. Because if the media does not exist, it will hamper a learning process. What inhibits the absence of media, namely when the budget is late given and poor budget management.